Improved corrosion inhibition effect of a green three-component compound to Q235 steel in acidic solution - Chengjia Bao; Weijian Qi; Zhuanjun Zhu; Ting Xu; Long Zhao; Yanhong Ma; Yang Liu; Bowen Yang; Xueru Luo; Hui Yun; Xiaojuan Li (Results in Chemistry)
Chitosan (Chi), curcumin (Cur) and geraniol (Ger) are natural compounds, which can potentially serve as green corrosion inhibitors. Herein, the corrosion inhibition efficiency (IE) of them was compared. The corrosion rate of 1.5 mM Chi on the 1 st d was 0.78 ± 0.41 g/ (m2 h), significantly lower than that of the control group (CK) (2.59 ± 0.32 g/ (m2 h)), while the corrosion rate of 2 mM Cur decreased by 8.48–18.71 times. The corrosion IE of 1.5 mM Ger remained above 60 % for over 15 days. To improve corrosion IE on Q235 steel in acidic solution, two-component and three-component compounds of them at their optimal IE concentrations were also tested and evaluated by weight loss and electrochemical analysis. Chi+Cur + Ger exhibited the minimum growth rate of corrosion rate (0.19–15.36 g/ (m2 h)) and the maximum corrosion IE (81.87–96.41 %) during 20 days. The weight loss was 20.65 % of the control on the 20th day. The Tafel results indicated Chi+Cur + Ger functioned as a mixed-type corrosion inhibitor, inhibiting the cathodic reaction more significantly. The surface observation and X-ray photoelectron spectroscopy (XPS) proved the formation of an adsorption layer on the steel surface. Chi and Cur could adsorb on the steel surface through chemical interaction like by amine and/or hydroxyl groups, while Ger through physical adsorption. The synergistic anticorrosion layer not only prevented steel surface from corrosive solution attack, but also increased the resistance to retard the charge transfer in the solution. The results might shed new insight in the application of green complex for steel corrosion inhibition.